Passion & purpose : stories from the best and brightest young business leaders - Coleman, John, 1981-; Gulati, Daniel; Segovia, W. Oliver (Boston, Mass. : Harvard Business Review Press, 2012)
Provides an overview of the big issues in the business world today, with firsthand accounts from young leaders tasked with tackling these issues head on.
From questions about globalization and sustainability to issues surrounding diversity, learning, and the convergence of the public and private sectors, tomorrow's leaders have a lot to think about. But these big issues aren't the only ones facing young leaders starting out in business today. What else are they focused on? And how do they prioritize the challenges and opportunities before them--while also making the world a better place? In Passion & Purpose, recent Harvard Business School MBAs share personal stories about assuming the mantle of leadership in ways unlike any previous generation. IN candid, often moving accounts of their successes and setbacks--from launching start-ups or taking on the family business to helping kids in the Arabian Gulf or harnessing new technology to develop clean energy--they reveal how their generation's ideas, aspirations, and practices are radically reshaping business and transforming leadership. Drawing on insights from a survey of five hundred students from top U.S. business schools, Passion & Purpose provides an overview of today's big hot-button issues, followed by firsthand accounts from the young leaders who are tackling these issues head-on. Their personal stories are rounded out with broader perspectives from established luminaries in business, academia, and the public sector, including Dominic Barton (Global Managing Director of McKinsey & Company), Deb Henretta (Group President of Proctor & Gamble Asia), Nitin Nohria (Dean of Harvard Business School), David Gergen (Director of the Center for Public Leadership at the Harvard Kennedy School, senior political analyst for CNN, and former presidential adviser), Carter Roberts (President and CEO of World Wildlife Fund), Joe Kennedy (CEO and President of Pandora), and RIch Lyons (Dean of Haas Business School, University of California-Berkley).
Floating above the boxes : business, nonprofit, and the age of falling boundaries / Umaimah Mendhro -- Learning from Kibera : nonprofit lessons for business from East Africa's largest slum / Rye Barcott -- Commerce and Culture : combining business and the arts / Christina Wallace -- Iraq, Afghanistan, and the business of peace / Jake Cusack -- Business in the world : how corporations can be change agents / Kelli Wolf Moles -- Interview with David Gergen, adviser to four presidents, Director of Harvard's Center for Public Leadership, and senior political analyst for CNN -- Bridging two worlds : an India story / Sanyogita Aggarwal -- Qatar debate : education, civic engagement, and leadership in the Arabian Gulf / Andrew Goodman -- Emerging social enterprise : learning the business of agriculture in Tanzania / Katie Laidlaw -- Global citizen year : learning from the world / Abigail Falik -- The business of reconciliation : how cows and co-ops are paving the way for genuine reconciliation in Rwanda / Chris Maloney -- Interview with Dominic Barton, Global Managing Director of McKinsey & Company -- Nonconforming culture : how to feel comfortable in who you are no matter where you are / Kimberly Carter -- Diversity Day : whole people, whole organizations, and a whole new approach to diversity / Josh Bronstein -- Women and the workplace / Tasneem Dohadwala -- Joyful on the job : a generation pursuing happiness at work / Benjamin Schumacher -- People leadership from Baghdad to Boston / Seth Moulton -- Interview with Deb Henretta, CEO, P&G Asia -- A sustainable career / Annie Fishman -- From safety nets to trampolines / Valerie Bockstette -- The value of community partnerships in addressing climate change / Charley Cummings -- Interview with Carter Roberts, CEO, World Wildlife Fund -- Building an online marketplace / James Reinhart -- Technology and social good : loans, relays and the power of community / Shelby Clark -- Mobile millennials / Jason Gurwin -- Interview with
Includes bibliographical references and index.
Description based on print version record.
Keywords: Leadership; Executives; Success in business; Organizational effectiveness; Leadership; Management; Success; Organizational behavior; Executives; Leadership; Organizational effectiveness; Success in business; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books